2022
DOI: 10.1088/1361-6455/ac9204
|View full text |Cite
|
Sign up to set email alerts
|

Paths from stationary to chaos in passively mode-locked fiber lasers: research progress of soliton pulsations and soliton explosions

Abstract: Research has shown that passively mode-locked fiber lasers produce chaotic output, which has caught the attention of physicists, chemists, and bio-scientists owing to their wide bandwidth, good random characteristics, and strong anti-interference. In passively mode-locked fiber lasers, soliton pulsations and soliton explosions with period bifurcation characteristics have been demonstrated to be effective paths to chaos as far as 20 years ago. However, due to the lack of real-time spectrum measurement technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 191 publications
0
11
1
Order By: Relevance
“…Such orthogonal linear polarized fields of DS with correlated phase relation can be treated as a general phase-coupled oscillator, as shown in Fig. 1(b) 34 , 37 , 40 , 41 . The slow temporal behavior of coupled oscillators strongly depends on syn-/desyn-chronization of orthogonal fields through a phase change.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such orthogonal linear polarized fields of DS with correlated phase relation can be treated as a general phase-coupled oscillator, as shown in Fig. 1(b) 34 , 37 , 40 , 41 . The slow temporal behavior of coupled oscillators strongly depends on syn-/desyn-chronization of orthogonal fields through a phase change.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Given the strong connection with the Fermi–Pasta–Ulam recurrence, 32 , 33 i.e., phenomena describing the periodic return of nonlinearly coupled oscillators to their original states, breather solitons, in addition to rogue waves emergence, turbulence, and modulation instability phenomena, have attracted considerable attention in nonlinear optics 6 10 , 32 , 33 Also, the breathing solitons are attractive because of their potential for metrology applications by enabling multiscale dual-comb sources for increased measurement resolution 34 . It was recently found that the breathing soliton emergence in anomalous dispersion MLLs can be driven by modulation instability 10 and a simultaneous effect of the soliton bunching and polarization instability 14 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations